1997
DOI: 10.1002/eji.1830271138
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immunoreceptor tyrosine‐based activation motif (ITAM) binding to ZAP‐70 by surface plasmon resonance

Abstract: The signaling function of the T cell antigen receptor (TCR) is mediated via CD3 polypeptides, the cytoplasmic sequences of which bear conserved immunoreceptor tyrosine-based activation motifs (ITAM). ITAM are defined by two YxxL/I sequences separated by a six-eight amino acid long spacer. Upon antigen recognition, ITAM become phosphorylated on both tyrosine residues, creating a high affinity binding site for the tandem SH2 domains found in the protein tyrosine kinase ZAP-70. Using surface plasmon resonance, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…The SH2-containing protein-tyrosine kinases ZAP-70 and Syk are the only effector molecules that associate in vivo with the phosphorylated form of ITAM-bearing molecules (33). The requirement of both tyrosines residues for complete KARAP/DAP-12 transducing function is consistent with the structure of ZAP-70 tandem SH2 domains, which dictates the simultaneous recruitment of both ITAM phosphotyrosines to a ZAP-70 SH2 tandem (34,35). The recently reported in vitro association between KARAP/DAP-12 phosphorylated peptides and ZAP-70/Syk is consistent with our in vivo point mutation analysis (26).…”
Section: Ubiquitous Expression Of Mouse Karap-itam-bearingmentioning
confidence: 61%
“…The SH2-containing protein-tyrosine kinases ZAP-70 and Syk are the only effector molecules that associate in vivo with the phosphorylated form of ITAM-bearing molecules (33). The requirement of both tyrosines residues for complete KARAP/DAP-12 transducing function is consistent with the structure of ZAP-70 tandem SH2 domains, which dictates the simultaneous recruitment of both ITAM phosphotyrosines to a ZAP-70 SH2 tandem (34,35). The recently reported in vitro association between KARAP/DAP-12 phosphorylated peptides and ZAP-70/Syk is consistent with our in vivo point mutation analysis (26).…”
Section: Ubiquitous Expression Of Mouse Karap-itam-bearingmentioning
confidence: 61%
“…These data may appear to be somewhat in contradiction with previous studies reporting similar affinities of the ZAP-70 and Syk proteins for the various TCR ITAMs. [31][32][33] Nevertheless, the aforementioned studies were performed in vitro with peptide ITAMs and not in a cellular context where many other variables come into play.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 It has previously been shown that both Syk and ZAP-70 bind to Lck [28][29][30] and that in vitro, the 2 kinases bind to chain ITAMs with similar affinities. [31][32][33] Indeed, it has been hypothesized that ZAP-70 may promote ITAM phosphorylation by bringing Lck into the TCR-chain complex. 28,34 In view of these data, it has been perplexing that chain phosphorylation is compromised in ZAP-70-deficient thymocytes and T cells expressing high levels of Syk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The truncated protein would have cellular activating properties, in contrast with its ITIM-bearing counterpart which would inhibit cell signaling through recruitment of SHP-1, SHP-2, or SHIP phosphatases (9) seemingly via their respective carboxyl-terminal SH2 domains (12,13). Human immunoreceptors map to the "complex" or "leukocyte receptor cluster" located on chromosome region 19q13.4 or to the natural killer complex on chromosome 12 (11).…”
mentioning
confidence: 99%